FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT KECEMASAN KELUARGA PASIEN YANG DIRAWAT DI INTENSIVE CARE UNIT (ICU) MURNI TEGUH MEMORIAL HOSPITAL - Lisma Wara Tambunan; Dior Manta Tambunan (Universitas Murni Teguh, 2026)
Anxiety can cause the individual to feel worried, afraid, anxious and can cause an increased heart rate. Anxiety is an emotional response that arises when a person is experiencing stress characterized by feelings of tension, worry, anxiety and accompanied by physical responses. The aim is to determine the factors that associated with an anxiety level of patient families in the ICU Murni Teguh Memorial Hospital. This research method is a quantitative study with a descriptive correlational design with a cross-sectional approach with a simple random sampling technique of 44 respondents. Data analysis used in this study is chi-square with the formula p <0.05 accepted or successful. The results show that there are several factors that associated with an anxiety level of patient families treated in the ICU Murni Teguh Memorial Hospital, namely gender with a p value = 0.030 <0.05, Education n = with a p value = 0.008 <0.05, occupation with a p value = 0.032 <0.05 and access to information p = 0.006 <0.05. Suggestions for future researchers are expected to conduct further research on the anxiety of patient families in the ICU using other variables so that they can complement the results of existing research.